Attitude Perspective in BBC News’ Article: An Appraisal Analysis - Entika Fani Prastikawati (Journal of English Language Studies, 2021)
Appraisal has been regarded as a way of negotiating the social relationship that also reflects how people feel about people and things. This current study presents the appraisal analysis through the system of meaning (attitude) in an article taken from BBC News. A discourse analysis was applied by evaluating the meaning behind discourse towards attitudinal perspective to figure the feelings out behind the discourse. The findings of this study revealed that effect of unhappiness was the most controlling attitude subsystems utilized and used in the BBC News’ article to convey the feeling of people and phenomena/events presented in the BBC News’ article. It was then followed by the realization of other attitude subsystems; judgment and appreciation. Point to the findings, those can be used as a teaching material of reporting news. Students may be taught how to write news using attitude words to show feelings.